Clinicopathological characteristics of T1 colorectal cancer without background adenoma. (27th February 2013) - Han, K. S.; Lim, S. W.; Sohn, D. K.; Chang, H. J.; Oh, J. H.; Lee, J. H.; Kim, H. R.; Kim, Y. J.
Abstract Aim Background adenoma (BGA) is defined as benign adenomatous tissue contiguous to resected carcinomas, and the absence of BGA in a tumour is considered a histological criterion of de novo cancers. The present study aimed to identify the clinicopathological characteristics of T1 colorectal cancer (CRC) without BGA. Method A retrospective review was carried out of prospectively collected data from two centres: the National Cancer Center, Korea; and Chonnam National University Hwasun Hospital, Korea. A total of 590 patients with T1 CRC, treated by endoscopic or surgical resection between January 2001 and August 2011, were enrolled. Details regarding gender, age, tumour location, endoscopic gross type, tumour size, depth of submucosal (SM) invasion, angiolymphatic invasion, tumour grade, budding and lymph node (LN) metastasis were evaluated with regard to the presence or absence of BGA. Results BGA was absent in 197 (33.4%) patients. Tumour size <20 mm, flat or depressed type, deep SM depth and tumour budding were associated with the absence of BGA in univariate and multivariate analyses (P < 0.05). In surgically resected patients, LN metastases were significantly associated with the absence of BGA (P = 0.022). Conclusion T1 CRC without BGA presented several characteristics of small size (<20 mm), flat or depressed type, deep SM depth (SM 2/3), LN metastasis and tumour budding. These results indicate that de novo cancers may have a more invasive potential.